THE EFFECT OF DERMAL APPLICATION OF BINAHONG LEAF EXTRACT OINTMENT ON INCISION WOUND - Samirana, Putu Oka; Sudimartini, Luh Made; Sumadi, I Wayan Juli; Wilantari, Putu Dessy (Buletin Veteriner Udayana, 2022)
Incision wound are injuries that caused by sharp instruments, for example wounds that occur after surgery. This study aims to determine the effect of Binahong leaf extract ointment on incision wound healing. Anredera scandens (L.) Moq. extracted using ethanol 70%, then made an ointment on the basis of adeps lanae and vaselin album. A total of 35 female white wistar rats aged 2-3 months with a weight of 200 g and acclimatized for one week, arranged to 7 the tratments groups. All groups made incision wounds on the back parallel to the vertebrae. Everyday given 250 mg of ointment twice a day. After given the ointment, then parameters observed from histopathology of the skin were infiltration of inflammatory cells and the formation of collagen. The results showed that on the the 21 st were still inflammation cells that were not significantly different (p>0,05) in all groups and at 40% extract concentrations a significantly different formation of collagen occured (p<0,05). In conclusion, the ethanolic leaf extract of A. scandens (L.) Moq. not able to reduce inflammation cells after 21 days of treatment and at a concentration of 40% showed the most significant collagen formation.